Estudo linguístico no Vale do Jequitinhonha: o léxico de Minas Novas - Maryelle Joelma Cordeiro (2013)
This work presents the study of the rural vocabulary of Minas Novas, located in the Vale do Jequitinhonha in Minas Gerais. The choice of this region was made for several reasons, among them: a) the considering aspects of the local culture; b) the kind of occupation of the region by the means of mining; c) the perception of many peculiarities in speech ofresidents. Our analysis aims to show the strong relationship between language, society and culture. As for theoretical support we relied on Sociolinguistics (Labov, 2008; Milroy, 1987 and Milroy, 1992), on the Lexicology and on the Lexical fields theory (Biderman, 1978, 1998, 2001, 2002) on Anthropological Linguistics (Duranti, 2005 ) and on the concept of "Cultural region" (Diégues Jr., 1960). Following the labovian methodology, recordings were made with residents of the ruralarea with specific profile tailored previously by predetermined norms. Then, the interviews were transcribed and the transcripts were selected by the vocabulary that best characterized the local reality, the rural environment. For each lexical unit chosen was elaborated a lexicographic sheet containing information relating to its definition and origin. From the data was made quantitative and qualitative analyzes and finally was made a glossary with linguistic information, definitions and accreditations, providing thus, in the future, easier queries for the selected vocabulary.